2007
DOI: 10.1007/s10152-007-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Sublittoral soft bottom communities and diversity of Mejillones Bay in northern Chile (Humboldt Current upwelling system)

Abstract: The macrozoobenthos of Mejillones Bay (23°S; Humboldt Current) was quantitatively investigated over a 7-year period from austral summer 1995/1996 to winter 2002. About 78 van Veen grab samples taken at six stations (5, 10, 20 m depth) provided the basis for the analysis of the distribution of 60 species and 28 families of benthic invertebrates, as well as of their abundance and biomass. Mean abundance (2,119 individuals m ¡2 ) was in the same order compared to a previous investigation; mean biomass (966 g form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
2
40
0
1
Order By: Relevance
“…Positive effects of EN events on macrozoobenthos communities have been previously reported for the upwelling systems along the Peruvian coast (Tarazona 1984;Tarazona et al 1985Tarazona et al , 1988aTarazona et al , 1996Arntz et al 1991;Arntz and Fahrbach 1996; but see Yupanqui et al 2007), north (Laudien et al 2007) and central Chile (Gallardo 1985;Gutiérrez et al 2000), and were generally suggested to be related with increased water temperature and dissolved oxygen during EN. However, as far as we are aware, no previous studies had reported the potential of this oceanographic anomaly to affect species assembling processes in marine benthic communities.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Positive effects of EN events on macrozoobenthos communities have been previously reported for the upwelling systems along the Peruvian coast (Tarazona 1984;Tarazona et al 1985Tarazona et al , 1988aTarazona et al , 1996Arntz et al 1991;Arntz and Fahrbach 1996; but see Yupanqui et al 2007), north (Laudien et al 2007) and central Chile (Gallardo 1985;Gutiérrez et al 2000), and were generally suggested to be related with increased water temperature and dissolved oxygen during EN. However, as far as we are aware, no previous studies had reported the potential of this oceanographic anomaly to affect species assembling processes in marine benthic communities.…”
Section: Discussionmentioning
confidence: 68%
“…McPhaden (1999) suggested that 1997-1998 ENSO to be the strongest on record. According to some physical indices however, the biological impact of El Niño (hereafter EN) on northern Chile and South America in general was not as catastrophic as generally expected (Arntz et al 2006;Laudien et al 2007). This does not only hold true for softbottom communities (Laudien et al 2007), but also for the pelagic ecosystem of the same area (Ulloa et al 2001).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Molluscs are an important component of benthic faunas in sandy marine sediments in terms of abundance and biomass (Cadée 1968;Troncoso and Urgorri 1993;Lourido et al 2006;Laudien et al 2007), and its study may provide valuable information about the state of benthic assemblages and environmental conditions (Bresler et al 1999;Nehring 2005;Amin et al 2009). Gastropods inhabiting subtidal soft bottoms have a great influence on the populations of other benthic animals; for instance, naticids and retusid opistobranchs are active predators of bivalves, and turrids prey on small polychaetes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the normally stable thermal regime of the HCS and the strong thermal anomalies associated to the extremes of ENSO, temperature has been proposed as a key factor driving changes at the population and community level, and thereby influencing community structure and the latitudinal distributions of marine benthic organisms within this system (e.g. Soto, 1985;Tomicic, 1985;Arntz and Fahrbach 1991;Díaz and Ortlieb, 1993;Urban, 1994;Laudien et al, 2007). Unfortunately, cause-and-effect explanations of the described changes during extremes of ENSO are hampered by the lack of experimental and physiological evidence (Arntz et al, 2006;Thatje et al, 2008).…”
Section: Introductionmentioning
confidence: 99%